Caracterización geomorfológica de los ríos de Galicia mediante unidades litotopográficas - García, Jesús Horacio (Geographicalia, 2014)
A lithotopo unit definition proposal is made for Galicia. A lithotopo unit will be defined as a sector with equal topography and lithology, therefore, as an area where the ecological processes display similar behaviours. This definition allows the segmentation of rivers as well as the classification of fluvial systems. The lithotopo units have been developed from cartographic analysis, using multivariate techniques for two variables: topography (elevation, slope and roughness) and lithology. Next, several geomorphic parameters (channel slope, hydraulic radius, width/depth ratio of the channel, sediment median size and specific power) were measured in twenty-three working sectors along the Cabe River (Lugo, NW Spain) which encompass different lithotopo units. The results show that the geomorphic descriptors for each lithotopo unit vary within a similar range of values. This range is enough to allow their identification as internally homogeneous and mutually distinguishable units. The territorial mapping into lithotopo units makes it easier both to implement management measuresand to make comparisons between fluvial systems.
Keywords: Lithotopo unit; fluvial geomorphology; hydromorphological characterization; fluvial classification; Water Framework Directive (2000/ 60/CE); Galicia (NW Iberian Peninsula)